DEVELOPMENT OF STUDENT WORK SHEET BASED ON SOFT SKILLS ON COLLOID MATERIALS CLASS XI HIGH SCHOOL - Ruku, Ellen Cristy; Rusmini, Rusmini (JCER (Journal of Chemistry Education Research), 2019)
The purpose of the research is determine the feasibility of the student worksheet based on soft skills on the subject matter of colloids in terms of content validity and construct through the results of expert validation, practicality through student activities and student responses and effectiveness through student learning outcomes and the assessment of students' soft skills. This type of research is a 4-P model development research with stages, namely, defining, designing, developing, and dessiminate, which is limited to the development stage. A limited trial was conducted to 15 students of 11th grade in SMA Negeri 1 Bangsal Mojokerto. The results showed that the worksheet developed valid in terms of content validity obtained a percentage of 91.76% and construct validity obtained a percentage of 92.49%. Practical in terms of the results of student responses to the worksheet obtained a percentage of 97.16% and supported by observations of activities students get a percentage of 92.27%. Effectiveness in terms of student learning outcomes obtained a value of ? 70 with classical completeness of 100% and the assessment of soft skills of students gained a percentage of 92.41% so that students have the ability to entrepreneurship.